Childhood, adolescence and apprenticeship in Barcelona. The notarial sources of the Santa Creu Hospital (15th century) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2024)
The wealth of notarial registers of the Santa Creu in Barcelona makes it possible to develop in-depth research on the daily life of the city's main hospital. On the basis of the systematic analysis of the twelve surviving manuals notarials (1401-1501), both edited and unpublished, it was possible to analyse in detail the types of contracts concerning adoption, fostering and apprenticeship in late medieval Barcelona. In this respect, the comparative analysis between the Catalan example and that of other cities (such as Florence, Milan, Naples, Rome and Valencia) suggests new insights into the evolution of notarial and fosterage practices in the Western Mediterranean between the Middle Ages and the Modern Age. Structured in two main parts, the first describes the sources and types of contracts consulted, while the second presents new data resulting from the perusal of notarial documentation, in an attempt to get as close as possible to the reality of the many lives of the infants of Barcelona.
Keywords: Childhood; Apprenticeship; Medieval hospitals; Barcelona; Late Middle Ages